Reviu Strategi Pencegahan Perilaku Berisiko pada Pemuda di RPJMN 2020—2024 - Indra Nugroho (Kementerian Koordinator Bidang Pembangunan Manusia dan Kebudayaan Republik Indonesia, 2021)
The youth oath was present 93 years ago on the basis of the same understanding of the diversity of customs, tribes, cultures, languages to fight for Indonesian independence and against invaders. After 93 years of youth vows passed the youth of Indonesia are faced with a very different threat that is no longer a literal invader but a 'colonization' from the physical and psychological side of youth including the impact of technological developments. Currently youth are faced with the threat of risky behaviors such as narcotics abuse, psychotropic, and other addictive substances (NAPZA), risky sexual behavior, violence and bullying, which can all hinder youth from doing their job as the next generation of qualified nations. Through RPJMN 2020-2024, in the framework of quality human resource development, the government has determined one of its priority projects is improving youth quality, with one of three existing strategies being the prevention of risky behavior in youth. This paper analyzes whether the government's strategy through the prevention of risky behavior in youth is appropriate to answer the development of quality human resources. This study uses a qualitative approach that is case studies. Three theories are used in the analysis of this paper: prevention theory, behavioral theory and risk theory. The study concluded (3) important findings. First, the project specified still dwells on the second quantity aspect, the quality of socialization and education is still limited in scope, and third, there is no special study of the root cause. Thus, improvements are needed in the government's work plan going forward, particularly about the selection of projects that support in the prevention of youth risky behavior. Risky behavior prevention strategies in youth will improve the quality and capacity of Indonesian youth to meet the demographic bonus in 2030 and Indonesia gold in 2045 through risky behavior prevention strategies in youth.